Study of northern Evia's ultramafic rocks as skid-resistant aggregates in pavement construction mountain (central Greece): correlations and evaluation - Kosiari, S. (Bulletin of the Geological Society of Greece, 2007)
The study presented in this paper addresses the low skid-resistance factors measure d throughout the Hellenic road network. These low factors are mainly traced to the use of limestone as aggregate resource. The study is mainly focused on the capabili ty ofperidotite ofPapades region (N.Evia), to be used as aggregate resource since this rock is harder and thus more skid-resistant. Mechanical, petrographical and m ineralogical tests have been conducted in order to determine its suitability for skidresistant aggregates in pavement construction, according to Greek and Internation al standards and specifications.